Voluntary disclosures and climate change uncertainty: Evidence from CDS premiums - Imerman, Michael B.; Ye, Xiaoxia; Zhao, Ran (Journal of Corporate Finance, 2025)
We examine the effect of voluntary climate risk disclosure on Credit Default Swap (CDS) premiums. We develop a structural model, in which climate-related disclosures serve as an information source reducing climate change uncertainty. The model predicts a negative relation between the informativeness of climate risk disclosure and the CDS premium, and asymmetric effects of positive and negative disclosure tone on the CDS premium. Using climate risk measures quantified from earnings call transcripts, we provide evidence supporting these predictions with causal inference. Our study suggests that climate risk is priced in the CDS market, where investors pay attention to climate risk disclosures.